Innovation and Shelf-Character: The Way of Organizational Existence in the Pandemic Era - Hendra Suwardana; Anggia Kalista (INNOVATION RESEARCH JOURNAL, 2021)
The Covid 19 pandemic has awakened the organizing of organizational life as an entity that is believed to be well established, but in fact absurd. This certainty belongs only to change itself. The ability to adapt to the surrounding environment by adopting its wisdom values which are contained in a series of continuous innovations can ensure the existence of organizational life to grow and develop throughout the ages. Innovation as an investment value can thrive both in an organization when there are leadership souls individually or in a hierarchical leadership that is open - minded and has a strong self- character to be willi ng to accept input from subordinates and be able to observe current developments that are needed by the market. On this day an organization if it does not want to adopt the value of innovation is the same as going to its death path slowly, so that the choice is to innovate or die.